Genetic characterization drives personalized therapy for early-stage non-small-cell lung cancer (NSCLC) patients and survivors with metachronous second primary tumor (MST): A case report. Issue 10 (March 2017) - Ding, Xingchen; Wang, Linlin; Liu, Xijun; Sun, Xindong; Yu, Jinming; Meng, Xue
Abstract: Rationale: The pathogenesis and progression of lung cancer is a complicated process in which many genes take part. But molecular gene testing is typically only performed in advanced-stage non-squamous non-small-cell lung cancer (NSCLC). The value of tyrosine kinase inhibitors (TKI) administration is not widely recognized with respect to early-stage NSCLC. Patient concerns: Here, we present a case of a man, heavy smoker who initially presented with stage IA lung adenocarcinoma (LADC). Three years after a lung lobectomy, he was diagnosed with advanced lung squamous cell carcinoma (SCC), according to laboratory, imaging, and pathological examinations. Diagnoses: The case initially had an early-stage LADC with an L858R epidermal growth factor receptor (EGFR) mutation. A subsequent advanced SCC bearing EGFR L858R/T790M mutations occurred 3 years after surgery. Interventions: The comprehensive therapy we utilized, including surgical resection for the early-stage lesion and GP chemotherapy and local radiotherapy as the first line therapy along with gefitinib maintenance treatment for the advanced metachronous second primary tumors (MST). Outcomes: The synthetical therapy, have resulted in our patient with remaining alive and progression free for 4.5 years. Lessons: This case suggests that changes in molecular pathology should be monitored closely throughout cancer progression to guide personalized therapy and improve prognosis. We further review administration of TKI to early-stage NSCLC and to the metachronous second primary tumors (MST) in survivors.